Special coffee: alternative for coffee growing in Risaralda (2021)
As a reaction to the deep crisis caused by the breaking of the quotas pact in 1989, new searches begin for the generation of added value to Colombian coffee in which are included specialty coffees. The article shows its overall progress and the specific behavior in the Department of Risaralda. It is concluded that this type of coffee growing, requires deep changes, but at the same time it can become an alternative for its permanence and continuity.